Rapid and Sensitive Determination of Lipid Oxidation Using the Reagent Kit Based on Spectrophotometry (FOODLABfat System) - Chang Woo Kwon; Kyung-Min Park; Jeong Woong Park; JaeHwan Lee; Seung Jun Choi; Pahn-Shick Chang (Journal of Chemistry)
The reliability and availability of FOODLABfat system for determining acid value (AV) and peroxide value (POV) were assessed during the hydrolytic rancidification and lipid oxidation of edible oils. This reagent kit based on spectrophotometry was compared to the official methods (ISO 660 and 3960 protocols) based on manual titration employing the standard mixture for the simulated oxidation models and edible oils during the thermally induced oxidation at 180°C. The linear regression line of standard mixture and the significant difference of thermally oxidized time course study determined between them showed high correlations (R2=0.998 and p<0.05) in both AVs and POVs. Considering ISO protocols with a probability of human error in manual titration, the rapidness and simplicity of the reagent kit based on spectrophotometry make it a promising alternative to monitor the lipid oxidation of edible oils and lipid-containing foods.